The 0.0003 percent: Short-run dynamics of extreme wealth in America - Arshad Mirza; Nirvikar Singh (University of California, Economics Department, 2019)
This paper analyzes the short-run dynamics and changing sources of wealth among the Forbes 400 list of the wealthiest individuals in the United States, using annual data for 12 years spanning before and after the financial crisis of 2008-9. Over the entire time period the growth of wealth was negatively related to the previous years' wealth, implying a slight degree of wealth convergence within the group. We find that the overall growth of the group's wealth slowed after the crisis but stayed well above the GDP growth rate. Considering the interaction of growth of wealth with personal characteristics, we find that those who can be classified as self-made had a higher average wealth growth rate than their counterparts, although this lead narrowed after the financial crisis, during the Great Recession. Similarly, those with advanced degrees also had higher average growth of wealth in the pre-crisis period. We also examine the mobility of in and out of the Forbes 400, and find that turnover was higher in the period prior to the financial crisis, particularly for self-made individuals and those with advanced degrees. The self-made were also more likely to rise in rank within the Forbes 400 conditional on persisting in the list. By employing an innovative method of dealing with selection bias in a truncated panel, we are able to ascertain that our results are not driven by these biases. We also find some differences in these patterns at the sectoral level, compared to the aggregate group.
Keywords: J11; I24; 330; Forbes 400; Financial Crisis; Great Recession; Income Inequality; WealthInequality; Higher Education